EVALUASI DAN TINGKAT PARTISIPASI MASYARAKAT DALAM PENGELOLAAN KAWASAN KONSERVASI MANGROVE DI DESA MUNTE KECAMATAN TANALILI KABUPATEN LUWU UTARA - Amnaeni Amnaeni; Asbar Asbar; Danial Danial (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2020)
Evaluation and level of community participation in the management of mangrove conservation areas in Munte Village, Tanalili District, North Luwu Regency. This study aimed to: 1) Evaluate the level of community participation in the management of mangrove; 2) Determine the direction of the mangrove ecosystem management strategy. In addition, it was expected to provide information to stakeholders as a material consideration in taking mangrove ecosystem management policies in Munte Village, Tanalili District, North Luwu Regency. The research method was done by using a questionnaire. The data on internal factors namely the characteristics of participants' dividends in the management of mangroves of the mangrove tourism area which was done by filling out questionnaires and interviews.The results Community participation in the 75% criterion had a high level of participation by showing that the average value of the linkert scale showed a positive range. 25% of criteria indicated a low level of participation with a negative range value, some people consider that mangroves had unimportant benefits for the farm. The management strategy based on the scale produced for the management of mangrove ecosystems in Munte, namely (1) Organizing training on mangrove management skills (ecotourism and nursery) to increase community income and (2) Making regulations to control the use of community-based mangroves and also violations mangrove management violations.